2010
DOI: 10.1016/j.ijrobp.2010.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Irradiation on Microvascular Endothelial Cells of Parotid Glands in the Miniature Pig

Abstract: Purpose To evaluate the effect of irradiation on microvascular endothelial cells in miniature pig parotid glands. Methods and Materials A single 25-Gy dose of irradiation (IR) was delivered to parotid glands of 6 miniature pigs. Three other animals served as non-IR controls. Local blood flow rate in glands was measured pre- and post-IR with an ultrasonic Doppler analyzer. Samples of parotid gland tissue were taken at 4 h, 24 h, 1 week, and 2 weeks after IR for microvascular density (MVD) analysis and sphingo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 26 publications
5
44
3
1
Order By: Relevance
“…Previously, we developed a mouse model of BRONJlike disease [6]; however, well-established large-animal models are needed for preclinical studies and will provide researchers with the opportunity to elucidate the mechanisms underlying BRONJ and to explore potential therapeutic approaches, particularly those that are difficult to implement in small-animal models such as rodents due to the small size of the orofacial region. Because of the high similarity between swine and humans in terms of histology and functions of the orofacial tissues [8,11,12], the miniature pig is increasingly used as a large-animal model for a variety of biomedical studies [13,14]. The findings from the present study showed that ZA treatment can suppress Treg levels in peripheral blood while increasing the levels of gdT cells and IL-17 in peripheral blood.…”
Section: Discussionmentioning
confidence: 55%
“…Previously, we developed a mouse model of BRONJlike disease [6]; however, well-established large-animal models are needed for preclinical studies and will provide researchers with the opportunity to elucidate the mechanisms underlying BRONJ and to explore potential therapeutic approaches, particularly those that are difficult to implement in small-animal models such as rodents due to the small size of the orofacial region. Because of the high similarity between swine and humans in terms of histology and functions of the orofacial tissues [8,11,12], the miniature pig is increasingly used as a large-animal model for a variety of biomedical studies [13,14]. The findings from the present study showed that ZA treatment can suppress Treg levels in peripheral blood while increasing the levels of gdT cells and IL-17 in peripheral blood.…”
Section: Discussionmentioning
confidence: 55%
“…We speculated that the increases of D* and f values in our study shared the same pathophysiologic mechanism. Although Xu et al reported that parotid microvascular density decreased at 4 h after RT [24], we considered the increase of blood volume secondary to vascular oedema to be the main effect of RT in the early phase of radiation-induced parotid damage. Furthermore, Lee et al documented a significant increase in parotid vascular plasma volume ( v p ) at 3 months after RT in patients with head and neck cancer, explained by vasodilatation and increased blood volume induced by inflammation [25]; we share the same opinion as them.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, although the differences are not statistically significant, earlier delivery of the Shh gene appears to result in better The microvascular damage by IR is a major cause of hyposalivation after IR. 8,19 SMGs collected 90 days after IR were examined for microvascular density (MVD) by IF against endothelial markers Aqp1 or CD31 as reported, 8,20 and the expression of Aqp1 protein was further quantified by Western blotting. IR significantly decreased Aqp1 + MVD and the expression of Aqp1 protein, whereas AdShh instillation on day 3 after IR significantly restored both indexes in SMGs of both sexes, and that on day 30 significantly preserved both indexes in males to a lesser extent but not significantly in females (Fig.…”
Section: Delivery Of Shh Gene Into Smgs Partially Rescues Irradiationmentioning
confidence: 99%